THE 3D DYSCALCULIA ASSESSMENT GAME FRAMEWORK FOR DYSCALCULIA IDENTIFICATION - PUDJOATMODJO, BAMBANG; Salam, Sazilah; Che Pee @ Che Hanapi, Ahmad Naim; Rikman, Aherliwan Rudavan; Setijadi, Prihatmanto; Ashraf, Alomoush (University of Bahrain, 2022)
Dyscalculia is a hidden disability and may happen to ordinary people whether they are normal or highly intelligent students. This makes dyscalculia is challenging to identify. One method to identify dyscalculia students could be through playing games. Games concept could make the students do not feel of being tested when they are doing the test. Developing the game to fulfill the assessment purposes needs a framework that is designed for assessing. Design Play Experience (DPE) is an existing framework that supports the creation of a serious game or game-based learning. The framework contains several layers, such as learning, storytelling, gameplay, user experience. The purpose of the framework is to give a player experience in improving their skills. In this study, the DPE framework is adapted and enhanced to provide a serious game framework for assessing, identifying and monitoring dyscalculia students. The assessment result will be used to identify whether or not the student has a learning difficulty in mathematics. The enhanced framework is called 3D Dyscalculia Assessment Game (3DAG). Games that are applied with the 3DAG framework will notify where the students misconception are, so that the teacher can monitor and improve their mathematics accordingly.